Program Magang di Rumah Rakyat: Membangun Citra Positif Dewan Perwakilan Rakyat Republik Indonesia - Akbar, Yonarisman Muhammad; Rosadi, Raesita Rakhmawati; Royandiah, Ida (SIGn Journal of Social Science, 2024)
This study aims to analyze in depth the contribution of the Internship Program within the People’s House to building a positive image of the House of Representatives. The study employs a mixed methods approach with an explanatory sequential design, integrating qualitative and quantitative approaches. The first phase emphasizes a descriptive qualitative approach as the primary interpretative framework, collecting primary data through in-depth interviews with several key informants. Subsequently, the second phase utilizes a quantitative approach with a questionnaire instrument developed based on the qualitative themes identified in the first phase. The research population comprises alumni of the internship program, utilizing census sampling where the entire population is included as the sample. The results indicate that the Internship Program within the People’s House provides valuable practical experience for students and plays a crucial role in constructing a more accurate and positive public perception regarding the vital role of the House of Representatives in the Indonesian democratic system. The findings of this study demonstrate that political education, the direct involvement of the younger generation in the institutional processes of the House of Representatives, and targeted communication strategies are essential instruments in building public trust, increasing social capital, and strengthening the image of state institutions.